Asking Sentient Trees: Arabian Translations of East African Magic and Swahili Language in the Omani Empire - Almaazmi, Ahmed Yaqoub (2024)
Keywords: Moeurs et coutumes – Zanzibar; Occultisme – Oman

The Omani-Zanzibari Family: Between Politics and Pedigree in an Empire on the Rim - Abusharaf, Rogaia Mustafa (Hawwa, 2018)
Through a multi-sited ethnological lens, this article highlights the influences of political and economic dynamics on the Omani-Zanzibari family construction. It explores the fluid nature of the Omani-Swahili identity, the role of the family institution in regulating morality and sexuality, and the impacts of political events and forces on the development of multiple family configurations. It further analyzes key societal concepts such as marriage, legitimacy, succession, post-forced-displacement adaptation, and evolutionary identity. Through a qualitative study, the author uses fieldwork in Oman and Zanzibar, a range of primary archival sources, dialogues with prominent Omani-Zanzibari personalities, and published and private personal memoirs reflecting key historical periods in the development of Omani-Zanzibari identities to speak to the themes of the Omani polity that are unique to the Gulf.
Keywords: Moeurs et coutumes – Zanzibar